Implicit guarantees and the rise of shadow banking: The case of trust products - Allen, Franklin; Gu, Xian; Li, C. Wei; Qian, Jun “QJ”; Qian, Yiming (Journal of Financial Economics, 2023)
Implicit guarantees provided by financial intermediaries are a key component of China's shadow banking sector. We show theoretically that project screening by intermediaries, accompanied by their implicit guarantees to investors, can be the second-best arrangement and mitigate capital misallocation that favors state-owned enterprises (SOEs). Using a dataset of trusts’ investment products, we find, consistent with our model, that ex ante expected yields reflect borrower risks and implicit guarantee strength, and risk sensitivity is reduced by strong guarantees. Regulations in 2018 restricting implicit guarantees lead to a weaker relationship between yield spread and guarantee strength, and more credit rationing of non-SOEs.